Photocatalytic mineralization of organic acids over visible-light-driven Au/BiVO4 photocatalyst - Kanlaya Pingmuang (2018)
Au/BiVO 4 visible-light-driven photocatalysts were synthesized by coprecipitation method in the presence of sodium dodecyl benzene sulfonate (SDBS) as a dispersant. Physical characterization of the obtained materials was carried out by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), UV-Vis diffuse reflectance spectroscopy (DRS) and Brunauer, and Emmett and Teller (BET) specific surface area measurement. Photocatalytic performances of the as-prepared Au/BiVO 4 have also been evaluated via mineralizations of oxalic acid and malonic acid under visible light irradiation. XRD and SEM results indicated that Au/BiVO 4 photocatalysts were of almost spherical particles with scheelite-monoclinic phase. Photocatalytic results showed that all Au/BiVO 4 samples exhibited higher oxalic acid mineralization rate than that of pure BiVO 4 , probably due to a decrease of BiVO 4 band gap energy and the presence of surface plasmon absorption upon loading BiVO 4 with Au as evidenced from UV-Vis DRS results. The nominal Au loading amount of 0.25 mol% provided the highest pseudo-first-order rate constant of 0.0487 min -1 and 0.0082 min -1 for degradations of oxalic acid (C 2 ) and malonic acid (C 3 ), respectively. By considering structures of the two acids, lower pseudo-first-order rate constantly obtained in the case of malonic acid degradation was likely due to an increased complexity of the degradation mechanism of the longer chain acid. © 2013 Kanlaya Pingmuang et al.